A study on the application and effect of ERAS-based refined nursing in patients undergoing radical lung cancer surgery - Qi, Fang; Wang, Bin; Li, Xiangnan; Wang, Yan; Zhang, Jing (Frontiers in Surgery, 2025)
BackgroundIn recent years, the Enhanced Recovery After Surgery (ERAS) concept has gradually been applied in clinical practice. The aim of this study is to evaluate the impact of refined nursing based on the ERAS concept on clinical index, physiological index, and comprehensive health index of patients undergoing radical surgery for lung cancer.MethodThis study included 120 patients who underwent radical surgery for lung cancer. All patients were divided into an observation group (receiving refined nursing based on ERAS concept) and a control group (receiving routine care). Analyze the differences in clinical index, physiological index, comprehensive health index, and patient satisfaction at discharge between two groups before and after intervention. Evaluate the independent impact of nursing methods on these indicators through multiple linear regression. The ROC curve is used to evaluate the performance of a multi factor linear regression model.ResultThe observation group showed significant improvement in clinical index, physiological index, and comprehensive health index compared to the control group. In terms of complications, the incidence of pneumonia, pneumothorax and other complications in the observation group was significantly lower than that in the control group. The results of multiple linear regression analysis showed that ERAS based refined nursing had significant independent effects on clinical index, physiological index, and comprehensive health index. The ROC curve shows that the AUC of the biochemical indicator model is the highest, followed by the comprehensive health indicator and clinical indicator models.ConclusionThe refined nursing based on ERAS concept significantly improves the clinical index, physiological index, and comprehensive health index of lung cancer radical surgery patients compared to conventional nursing, and has the best effect in physiological index.